PENGARUH EKSTRAK DAUN BELUNTAS PLUCHEA INDICA L. TERHADAP PERTUMBUHAN GULMA MENIRAN (PHYLLANTHUS NIRURI L.) DAN TANAMAN KACANG HIJAU (PHASEOLUS RADIATUS L.) - FIDIAH ASTUTIK, ANIS Fidiah (LenteraBio: Berkala Ilmiah Biologi, 2012)
The aim of this study was to determine differences on the growth of weed P. niruri L. and P. radiatus L. due to the extract of the leaves of P. indica L. with different concentrations. The experiment was conducted at the green house. The Completely Randomized Block Design (RCBD) with one variable was used in this study, ie the concentration variable. The concentrations of leaves extract of P. indica L. were 0%, 0.5%, 1%, 1.5% and 2%. The growth parameters of P. radiatus L. and P. niruri L. measured were the height of the plant, the length of the root and the biomass of the plants. The data obtained were analyzed using analysis of descriptive using charts to determine the growth of P. radiatus and P. niruri. The results of this research showed that there was difference on the growth of both plants were affected by leaves extract of P. indica L. with different concentrations. The growth inhibition of P. niruri was greater than P. radiatus. The concentrations of leaves extract of P. indica showed that growth inhibition of P. niruri L. was 2%.